Stretching - Möglichkeiten und Grenzen - Freiwald, J.; Engelhardt, M.; Gnewuch, A. (Therapeutische Umschau, 1998)
The basic scientific knowledge about stretching remains incomplete in spite of its wide use in sports and physiotherapy. This article deals with the assessment of the flexibility and with the anatomical and physiological basis and limitations of stretching. The effects of stretching on delayed onset muscle soreness (DOMS), performance and regeneration are discussed. Recommendations are given for stretching as a measure of warming-up and cooling-down, for stretching before exercises, which demand explosive maximum muscle strength, and for stretching after training for strength endurance.